2020
DOI: 10.3390/insects11040243
|View full text |Cite
|
Sign up to set email alerts
|

Concanavalin A Toxicity Towards Potato Psyllid and Apoptosis Induction in Midgut Cells

Abstract: Concanavalin A (ConA), a legume lectin, has been drawing increasing attention in recent years concerning its toxicity against insects and its potential application in pest management. In an attempt to evaluate the effect of ConA on potato psyllid (Bactericera cockerelli), an economically important pest of solanaceous crops, the effect of ConA on potato psyllid survival, psyllid gut nuclear morphology, and expression of psyllid caspase genes were evaluated. Our results determined that artificial diet-feeding as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Simultaneously, our experiments showed that inhibitors of apoptosis, necrosis, and pyroptosis cannot reverse USIONPs-induced ferroptosis. However, ConA, a specific inhibitor of vacuolar type H + -ATPase activity (V-ATPase),which is capable of inducing apoptosis[ 36 ], promoted USIONPs-induced cell inhibitory rates unlike BAFA1 and CQ. These suggested that inhibitor of apoptosis couldn't reverse the USIONPs-induced ferroptosis, while apoptosis inducer may help USIONPs-induced ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, our experiments showed that inhibitors of apoptosis, necrosis, and pyroptosis cannot reverse USIONPs-induced ferroptosis. However, ConA, a specific inhibitor of vacuolar type H + -ATPase activity (V-ATPase),which is capable of inducing apoptosis[ 36 ], promoted USIONPs-induced cell inhibitory rates unlike BAFA1 and CQ. These suggested that inhibitor of apoptosis couldn't reverse the USIONPs-induced ferroptosis, while apoptosis inducer may help USIONPs-induced ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The dissected guts were fixed in 4% paraformaldehyde for 2 h at room temperature. After that, the guts were blocked by 5% bovine serum albumin in 1X PBS with 0.1% Tween 20, then incubated with TUNEL (terminal deoxynucleotidyl transferase dUTP nick end labeling) for 6 h as described in Tang et al (2020a) and Wang et al (2018) . TUNEL staining was performed using the In Situ Cell Death Detection Kit (Roche, Basel, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…We also used the apoptosis inducer Concanavalin A (ConA) by feeding, as a positive control. Following the protocol of our colleagues ( Sprawka et al, 2015 ; Tang et al, 2020a ) with modifications, the liquid diet used for psyllid feeding bioassays was prepared with a sterilized solution of 15% (w: v) sucrose and 1X PBS (Sigma-Aldrich, St. Louis, MO). ConA (MP Biomedicals, Solon, OH) was incorporated into the diet at a concentration of 2,000 μg/ml ( Sprawka et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…Development of strategies that induce apoptosis in the psyllid midgut, by manipulation of caspase genes, for example, may be a novel means to control acquisition and transmission of liberibacters by psyllids. For example, the legume lectin concanavalin A has been reported to induce apoptosis in the potato psyllid midgut when ingested from an artificial diet ( Tang et al, 2020 ).…”
Section: Vector Compatibility and Vector Immunitymentioning
confidence: 99%